Diseño e implementación de una estación de carga fotovoltaica aislada tipo Off-Grid para teléfonos móviles (2023)
The present project is framed in the current issue such as the use of clean renewable energy that is transformed into electricity, as a general objective the implementation of an isolated off-grid type photovoltaic charging station for mobile phones is proposed. The installation of this type of system will provide clean, safe energy and promotes the use of non-conventional energy, contributing to the reduction of polluting gases produced by the generation of conventional energies that affect the environment.